2018
DOI: 10.1159/000487380
|View full text |Cite
|
Sign up to set email alerts
|

Food Allergy Prevention and Treatment by Targeted Nutrition

Abstract: In view of the dramatic rise in the prevalence of food allergy globally, effective prevention strategies have become a public health priority. Several models have emerged around the etiology of food allergy, including the hygiene hypothesis, dual allergen exposure hypothesis, and vitamin D hypothesis. These form the basis for current and potential prevention strategies. Breastfeeding remains a key pillar of primary allergy prevention. Other nutritional interventions, including the use of whey-based, partially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 143 publications
0
27
0
4
Order By: Relevance
“…However, its effect on reducing the risk of AD has been reported in a meta-analysis ( 100 ) and in infants ( 102 ). No studies have reported the effect of supplementing strain-specific probiotics during pregnancy or early life in primary prevention of CMA ( 103 , 104 ). However, the effect of mixed strains of probiotics, or synbiotics (a mixture of pre- and pro-biotics) to achieve greater microbiota diversity has been shown to reduce the risk of necrotizing enterocolitis in premature infants.…”
Section: Primary Prevention Of Cmamentioning
confidence: 99%
See 1 more Smart Citation
“…However, its effect on reducing the risk of AD has been reported in a meta-analysis ( 100 ) and in infants ( 102 ). No studies have reported the effect of supplementing strain-specific probiotics during pregnancy or early life in primary prevention of CMA ( 103 , 104 ). However, the effect of mixed strains of probiotics, or synbiotics (a mixture of pre- and pro-biotics) to achieve greater microbiota diversity has been shown to reduce the risk of necrotizing enterocolitis in premature infants.…”
Section: Primary Prevention Of Cmamentioning
confidence: 99%
“…There are significant differences in the molecular weights and profiles of peptides in eHF ( 106 , 107 ). A task force of the European Academy of Allergy and Clinical Immunology (EAACI) has therefore called for stricter standards for the definition of eHF marketed in Europe, including preclinical testing, quality assurance, and labelling requirements ( 104 ). In 2016, DRACMA updated their recommendation to include the provision of rice hydrolysate in the first-line management in countries where this formula is available ( 108 ).…”
Section: Secondary Prevention and Management Of Cmamentioning
confidence: 99%
“…Independent of eczema severity, skin S. aureus colonization was associated with hen′s egg and peanut sensitization and persistent allergy, with a weaker association seen for cow′s milk, in a study that followed children from infancy to six years of age [ 106 ]. As a matter of fact, although strict allergen avoidance is still the key treatment for food allergy, there is a greater focus on the preventive effect of the addition of lactose and probiotics to hypoallergenic infant formulas in order to modulate the gut microbiome and early immune responses in high-risk populations, either in families with a history of allergies, or in infants who are showing evidence of food sensitization or eczema [ 28 , 107 ]. Only a few trials of probiotics for the prevention or treatment of challenge-proved food allergies have been published.…”
Section: Focus On Specific Allergiesmentioning
confidence: 99%
“…According to the vitamin D hypothesis, adequate vitamin D l and supplementation in the first year of life can sensitize children against allergen reduce the risk of development of food allergies and asthma [27]. On the other hand, levels of vitamin D may also increase the risk of allergic sensitization by inhibitin maturation of dendritic cells and the development of T-helper 1 responses [28]. Res into the gut microbiome and vitamin D is therefore considered to be promising fo understanding, treatment, and prevention of autoimmune and allergic diseases [29] The effects of hypovitaminosis D and dysbiosis on immune system are depict Figure 3.…”
Section: Linking Vitamin D the Microbiome And The Immune Systemmentioning
confidence: 99%
“…Nesse contexto, a utilização de probióticos parece ter efeito positivo em longo prazo, assim como a utilização de fibras prebióticas que serão fermentadas pelas bactérias da microbiota. A fermentação é que garante a produção dos AGCC que têm efeitos benéficos no controle de diferentes doenças inflamatórias 48,49,[50][51][52] ;…”
Section: Como Induzimos Na Prática Clínica a Tolerância De Mucosa Parunclassified